Study of Phytochemical Composition of Generative Organs of Standardized Drug Raw Material Crocus Sativus L (Global Journal of Science Frontier Research, 2018)
The article is devoted to the study of the development of methods for standardization of medicinal plant raw materials for the preparation of conditions for the maximum production of biological active substances from seed saffron.
Keywords: crocus sativus; hexane extract; benzene extract; chromatographic mass spectrophotometer